‘In-betweenness’ declared and confirmed: Zoë Wicomb’s October in the untightened grip of ethnic and national identification - Bartnik, Ryszard (Studia Anglica Posnaniensia, 2023)
The aim of this paper is to examine the concept of ‘in-betweenness’ as a potential frame of reference for Zoë Wicomb’s writing, particularly her latest novel October. Hence, my primary intent is to focus on the novelist as equipped with a faculty for crossing over separate cultural traditions and embracing different formative experiences. Interestingly enough, in this case, the notion of indeterminate identity begins from, yet is not limited to, a South African version of racial profiling. Therefore, the author’s interest in adaptable identities might be discussed apropos of skin color, but also in terms of oscillating between different geographical, cultural locations. In light of the above, a perspective accommodated here examines Wicomb’s thematization and confirmation of transitional experiences elaborated on a story of two females as becoming autonomous coloureds as well as mutable/unfixed/migrating characters. And, on top of that, this singular focus coincides with a broader pattern, filtered through the author’s aggregate account. As a person of South African descent, yet currently living in Europe, Wicomb acknowledges a specific adaptive domain, which in turn serves as a fitting backdrop for construing contemporary South African-ness from a more nuanced, in-between/cosmopolitan position.